Beneath the cuff: Often overlooked and under-reported blood flow restriction device features and their potential impact on practice—A review of the current state of the research - Rolnick, Nicholas; Kimbrell, Kyle; de Queiros, Victor (Frontiers in Physiology, 2023)
Training with blood flow restriction (BFR) has been shown to be a useful technique to improve muscle hypertrophy, muscle strength and a host of other physiological benefits in both healthy and clinical populations using low intensities (20-30% 1-repetition maximum [1RM] or < 50% maximum oxygen uptake [VO2max]). However, as BFR training is gaining popularity in both practice and research, there is a lack of awareness for potentially important design characteristics and features associated with BFR cuff application that may impact the acute and longitudinal responses to training as well as the safety profile of BFR exercise. While cuff width and cuff material have been somewhat addressed in the literature, other cuff design and features have received less attention. This manuscript highlights additional cuff design and features and hypothesizes on their potential to impact the response and safety profile of BFR. Features including the presence of autoregulation during exercise, the type of bladder system used, the shape of the cuff, the set pressure versus the interface pressure, and the bladder length will be addressed as these variables have the potential to alter the responses to BFR training. As more devices enter the marketplace for consumer purchase, investigations specifically looking at their impact is warranted. We propose numerous avenues for future research to help shape the practice of BFR that may ultimately enhance efficacy and safety using a variety of BFR technologies.